Combating and preventing criminal offenses against the environment in Ukraine - Marko, Sergii; Bondar, Volodymyr; Humenyuk, Mykhailo; Pavluk, Oleksandr (Universidad Hemisferios, 2025)
The article analyzes the current state and main directions of combating criminal offenses against the environment in Ukraine with an emphasis on legal mechanisms for information and analytical support. Therefore, the need to harmonize national practice with international standards of environmental safety and law enforcement is substantiated. It is determined that effective counteraction to such offenses requires a developed regulatory and legal framework for collecting, processing, systematizing and analyzing environmentally significant information. Likewise, the role of analytical intelligence and search as tools for predicting criminal activity and developing preventive measures is revealed. The relevance of legal regulation of the creation and functioning of specialized data banks, legal procedures for interaction between subjects of counteraction and the use of analytical activity results within criminal proceedings is emphasized. Moreover, the need for regulatory support for assessing the reliability of information used to identify and document environmental offenses is outlined. In that sense, special attention is paid to the implementation of innovative information technologies (IT) solutions and Geographic Information System (GIS) technologies as a legitimate means of environmental monitoring and recording criminal activity. Emphasis is placed on the importance of legal consolidation of algorithms for the use of unmanned aerial vehicles, thermal imaging control, and video recording of offenses. According to this, it is determined that the use of such technologies has not only evidentiary, but also preventive significance in the field of environmental protection. The conclusion is made about the need for a comprehensive approach, which includes regulatory, technical, and personnel support for analytical activities. The article contains proposals for improving the legal mechanism to prevent, detect, and investigate environmental crimes in Ukraine.